Elucidating Molecule–Plasmon Interactions in Nanocavities with 2 nm Spatial Resolution and at the Single‐Molecule Level. (2nd August 2019) - Zhang, Fan‐Li; Yi, Jun; Peng, Wei; Radjenovic, Petar M.; Zhang, Hua; Tian, Zhong‐Qun; Li, Jian‐Feng
Abstract: The fundamental understanding of the subtle interactions between molecules and plasmons is of great significance for the development of plasmon‐enhanced spectroscopy (PES) techniques with ultrahigh sensitivity. However, this information has been elusive due to the complex mechanisms and difficulty in reliably constructing and precisely controlling interactions in well‐defined plasmonic systems. Herein, the interactions in plasmonic nanocavities of film‐coupled metallic nanocubes (NCs) are investigated. Through engineering the spacer layer, molecule–plasmon interactions were precisely controlled and resolved within 2 nm. Efficient energy exchange interactions between the NCs and the surface within the 1–2 nm range are demonstrated. Additionally, optical dressed molecular excited states with a huge Lamb shift of ≈7 meV at the single‐molecule (SM) level were observed. This work provides a basis for understanding the underlying molecule–plasmon interaction, paving the way for fully manipulating light–matter interactions at the nanoscale. Abstract : Plasmonische Nanokavitäten beschränken Licht in einem kleinen Volumen und stärken die Wechselwirkung von Materie mit Licht. Die Einzelmolekülemission von Sonden an bestimmten Positionen in einer Nanokavität wurde gemessen, um die Molekül‐Plasmon‐Wechselwirkung besser zu verstehen.